Eradication of Helicobacter Pylori Infections and GERD: A systematic review and meta-analysis - Mou, Wen-Ling; Feng, Meng-Yao; Hu, Li-Hua (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study evaluates the association between the eradication of Helicobacter pylori (H. pylori) and gastroesophageal reflux disease (GERD). Materials and Methods: Relevant studies were identified by conducting literature search in PubMed, Cochrane, Embase, CNKI, VANFUN, and VIP databases. The prevalence rates of gastroesophageal reflux, heartburn, epigastric pain, and nausea were extracted from the identified research articles and were used in meta-analysis of relative risks (RR) to achieve an overall effect size of the relationship between H. pylori eradication and GERD. Results: A total of 19 randomized controlled trials were included in this meta-analysis. The prevalence of gastroesophageal reflux was significantly higher in patients with H. pylori eradication compared with patients without it (RR: 1.54, 95% CI: 1.06-2.24; p=0.02). A subgroup analysis did not identify any significant difference in GERD prevalence in studies conducted outside China (RR: 1.62, 95% CI: 0.98-2.68) or in China (RR: 1.30, 95% CI: 0.76-2.22). There were no significant differences in heartburn (RR: 1.03, 95% CI: 0.88-1.20), epigastric pain (RR: 0.98, 95% CI: 0.13-7.56), or nausea (RR: 0.44, 95% CI: 0.07-2.72) risk between patients with and without H. pylori eradication. Conclusion: Eradication of H. pylori infection is found to be associated with GERD, although regional differences may exist in the prevalence. Well-designed studies especially those with stratification of patients’ basic conditions are needed to seek refined evidence of the association between H. pylori eradication and the GERD.